Starting up - Cao Thuy Dung (2017)
In this project, we explore the startup ecosystem in Singapore by talking to its key stakeholders: the government, investors, and entrepreneurs. We look into different parts of the startup ecosystem, such as incubation, acceleration, fund acquisition, and startup culture, as a guide for aspiring entrepreneurs to begin starting up.